(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This is true for every business deal that a firm makes these days, irrespective of which sector it is in. It also has a relationship with clients in an age where there is every company organisation due to existence. Another thing is the company’s mission statement on continuous development and world-class competition for client satisfaction. Hence, CRM has been one of the preferred concepts in recent economic times. All these things are built around a technology that is in vogue for pulling in new customers and holding existing ones at bay. In the services sector, it is common to use CRM extensively because it promotes customer happiness, retains customers, and creates permanent customer relations that generate profits over time. This research that is going to be undertaken will provide insights on how the hospitality industry leverages technological innovations to improve customer relations. The main purpose of this research is to understand how CRM technology can be strategically employed to reform hospitality services in India and in hotels. Using secondary data, this research assesses how innovative the hotel industry is in India in terms of knowledge levels.